THE DEVELOPMENT OF PRAYING ABILITY SCALE FOR MUSLIM WITH DIABETIC FOOT PROBLEM - Jasfizal J; Y, Nazri; M, Ramli (International Journal of Allied Health Sciences, 2019)
Solah or prayer is one of the pillars of Islam and a fundamental component of Ibadah. Muslim prayer involves physical motions and recitations. It requires cleansing of the body, ablution, and proper clothing before the prayer. In Muslim patient who has a diabetic foot problem, most of them having difficulty in doing prayer due to their variety disability. This newly developed scale is meant to gauge their ability to pray objectively. Five experts each from orthopaedic, psychiatry, Islamic studies and science were gathered and construct the new scale to measure a Muslim ability to pray objectively. Nineteen items have been established to be tested. Two hundred twelve participants enrolled in this study which took place at IIUM Medical Centre and Hospital Tengku Ampuan Afzan. 125 participant is from the control group, while 87 participants are from the diabetic group. They were selected through stratified random sampling. The Kaiser-Meyer-Olkin (KMO) value was 0.72. The Exploratory Factor Analysis showed the 19 items of praying ability scale composed of five domains with three items in each domain. Cronbach’s alpha values on finalised 19 items were 0.788, which signify good scale reliability. All of the items showed good factor loadings of more than 0.5.The five identified domains are namely Preparation of praying (factor 1), Physical movement (factor 2), Spirituality (factor 3), Engross & Tayammum (factor 4) and Disturbance (factor 5). The individualised Cronbach’s alpha of each domain ranged from 0.67 to 0.903. This study has proved that the new Praying Ability Scale (PAS) is valid and reliable to be used as tools to measure prayer ability in diabetic foot patient.